Hermeneutika Komunisme Primitif - Alam Mahadika (Indonesian Journal Publisher, 2022)
This study aims to describe a more conceptual understanding of the Hermeneutics of Primitive Communism, using qualitative research with a socio-historical approach that analyzes the condition of language data and behavior in situations that consider the social and cultural context. In special needs, the survey results are obtained, for example, analyzing the results of the theories of primitive communal theory until the discovery of the primitive communist epistemology. The findings of this socio-historical research are that the explanation of Primitive Communism Hermeneutics has three first stages, primitive communalism or primitive communism called primitive society, the basic needs of life that depend on nature, primitive communism is in people who live by hunting with simple forms of agriculture, or herding animals. , the state of private property has not arisen, and there is not even a class division. People live in harmony and equality. Even as primitive communism, the means of production are collectively owned, and other types of property are distributed equally among the members of the tribe. After that, the birth of Pre-Marxism, namely after the life of primitive society, with the emergence of the classical period rejecting metaphysics and visible psychology of collective and individualist society. The last is the development of Karl Marx's ideas which wants a communist society through resistance by the feudal society and capitalism using a system of socialism.